Clinicopathological features and prognosis of ciliated muconodular papillary tumor - Kang Shao; Yalong Wang; Qi Xue; Juwei Mu; Yushun Gao; Yonggang Wang; Bingzhi Wang; Lina Zhou; Shugeng Gao (Journal of Cardiothoracic Surgery, 2019)
Abstract Backgrounds The pulmonary ciliated muconodular papillary tumor (CMPT) is a very rare tumor with only several case reports in published literatures, and its clinicopathological features, standard treatment methods and prognosis has not been well defined. Methods Two cases of CMPT diagnosed and treated in our hospital and 39 cases reported in the published literature were analyzed retrospectively. Results The cohort of 41 CMPT patients comprised of 20 males and 21 females, aged 9–84 years. The diameter of the primary tumor was 0.3–4.5 cm. Most of these lesions were subsolid nodules, as observed on computed tomography and easily misdiagnosed as early lung adenocarcinoma. Tumors of 26 patients were stained by immunohistochemistry method, which revealed that CK7, CEA, and TTF-1 were positive and CK20 was negative in most patients. The results of gene alternation demonstrated mutations in EGFR, KRAS, and BRAF and ALK rearrangements in CMPT. All the patients underwent surgical treatment and did not receive postoperative adjuvant therapy. The follow-up duration was 0–120 months, and no case of tumor recurrence was found until the final follow-up. Conclusions The incidence of CMPT was low and rate of image misdiagnosis high. Immunohistochemistry is helpful for accurate diagnosis of CMPT. Sub-lobectomy may be proper and adjuvant treatment should be avoided since the disease is now prone to benign lesions. Furthermore, since the biological behavior of this tumor is not yet fully elucidated, additional case data are essential for accurate conclusions.